Effects of the softening point of hydrophobic polymers on the salt-based filler used in antifreeze asphalt concretes. (June 2021) - Liu, Zhuangzhuang; Hoff, Inge; Sha, Aimin
Abstract: In order to investigate the effect of hydrophobic polymer softening points on salt-based fillers used in antifreeze asphalt concretes (AFACs), moisture absorption, salt-release property and thermal stability were studied and the performance of antifreeze and moisture susceptibility of AFACs were also assessed. Without preheating procedure, the softening point did not show a positive effect on the conductivity of modified salts, but changed the salt-releasing property after being mixed with the asphalt concrete. Further testing through simultaneous thermal analysis and scanning electron microscope has shown that the experience of high temperatures (between 100 and 200 °C) softens the small hydrophobic particles into thin layers coated on the surface of the salt, while hydrophobers decompose at temperatures above 200 °C. The result of heating cycles indicates that, based on the SEM observation, there are four situations of hydrophobic polymer particles on the salt surface. The salt-releasing property trends could be divided into three typical patterns. Generally, a higher softening point of hydrophober produces a better moisture susceptibility of the AFACs, while the pre-heating treatment on salts reduced the moisture susceptibility of AFACs. Graphical abstract: Unlabelled Image Highlights: A novel salt-based filler with surface modification was developed and to be contained in antifreeze asphalt concretes (AFACs). Softening point of modifiers, together with the heating treatment and heating cycles, affects the salt-releasing behavior, performing three typical patterns. Moisture susceptibility and antifreeze property of AFACs are associated with the softening point of hydrophobic polymer.